Human resources management strategy and its impact on achieving total quality management (Field study at Tishreen University) - جنبلاط, مادلين (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study aimed to demonstrate the role of the human resources strategy in achieving total quality management at Tishreen University. A set of recommendations have been reached that can show the impact of the human resources management strategy in reaching total quality management, as well as the need to adopt the total quality at the university. The descriptive and analytical approach and the method of convergence and deduction were used as a mechanism for study, and the questionnaire was relied on as a tool for measuring and collecting data. The most important results of the study is that there is a very strong correlation and a positive impact of human resource management strategies in total quality strategies at Tishreen University.